KONSEP INHADH IBNU ATHAILLAH AS SAKANDARI DALAM PROFESIONALISME GURU - Muhammad Husni (LP3M IAI Al-Qolam Malang, 2021)
The primary base of teachers or gurus are to grown the student’s morale construction. In other words, anything that becomes the standards of religious devotions also become the standards for exploring the knowledge. Knowledge shall be sincerely learned for seeking knowledge. Those sincere intention can become the very reason of exploring the knowledge as the spiritual process. Knowledge is always affiliates with devotion. In this term, learning, in the sufi’s way, is not only exploring for knowledge but also seeking of the truth. In seeking the truth as a spiritual process, character development should be grown in the soul. Character development through character education should be watering the soul and kindness in the heart. Because morale character is something which is radiate from the the soul. With this reasons, this research on sufism education system offers the bridge to those learning system. Because character education shall be implied with ascetic process to make heart and consciousness become pure. Key words: inhadh, teacher, education, professionalism, spiritual.